UPAYA WORLD WIDE FUND FOR NATURE (WWF) DALAM MENANGGULANGI PERDAGANGAN ILEGAL TRENGGILING INDONESIA KE CINA TAHUN 2014-2018 - Grinda Mersida, (2020)
The trade in protected wildlife is a contemporary crime that is still rife in the global order. Indonesia is one of the countries with the highest seizure levels of pangolins in Southeast Asia as a supplier of Sunda pangolins. Pangolin is one of the wild animals that has been included in the International Union for Conservation of Nature's red list as an endangered species that must be protected. Sunda pangolins are hunted and traded to various countries with the main destination country, namely China because demand is still very high. This problem is in the spotlight for environmentalists in the national and international spheres. Indonesia itself already has regulations related to illegal trade in wildlife. However, the applicable regulations have not been able to reduce the number of illegal confiscation and illegal trade, including pangolins. World Wide Fund for Nature (WWF) as one of the international organizations that focuses on the environment helps the Government of Indonesia in tackling this problem. This research will discuss the efforts made by WWF to assist the government in dealing with this problem using the theory of international organizations and international cooperation. The method used in this research is descriptive qualitative research method using data collection through literature studies obtained from primary sources that have been determined to support this research. Keywords: Sunda Pangolin, Illegal Wildlife Trade, World Wide Fund for Nature (WWF), International Organization